2017
DOI: 10.1108/imds-12-2015-0509
|View full text |Cite
|
Sign up to set email alerts
|

Predicting customer churn in mobile industry using data mining technology

Abstract: Purpose The purpose of this paper is to identify the influence of the frequency of word exposure on online news based on the availability heuristic concept. So that this is different from most churn prediction studies that focus on subscriber data. Design/methodology/approach This study examined the churn prediction through words presented the previous studies and additionally identified words what churn generate using data mining technology in combination with logistic regression, decision tree graphing, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 42 publications
2
27
0
2
Order By: Relevance
“…This study uses predictor variables such as devices used by customers, billing and charging customers, both voice and SMS data and internet usage. This is in general also consistent with research conducted by Govindaraju et al and Lee et al [6,7]. However, there are predictor variables that are not used in the Govindaraju et al such as number of days of service and data in each month, customer USIM usage, operating system of device used by customer and customer location for the first time [7].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This study uses predictor variables such as devices used by customers, billing and charging customers, both voice and SMS data and internet usage. This is in general also consistent with research conducted by Govindaraju et al and Lee et al [6,7]. However, there are predictor variables that are not used in the Govindaraju et al such as number of days of service and data in each month, customer USIM usage, operating system of device used by customer and customer location for the first time [7].…”
Section: Resultssupporting
confidence: 86%
“…However, there are predictor variables that are not used in the Govindaraju et al such as number of days of service and data in each month, customer USIM usage, operating system of device used by customer and customer location for the first time [7]. In addition there are predictor variables that cannot enter into Lee et al such as the length of time the customer, the number of days of service and data in each month, the purchase of credit by the customer, the duration of voice usage and the amount of SMS usage [6].…”
Section: Resultsmentioning
confidence: 99%
“…Both types of classifiers: single and ensemble have been used for churn dataset classification [22] and it was found that selforganizing map, Principal Component Analysis, and Heterogeneous Boosting outperform other classification methods. A study based on the text of customers for the consideration of their positive and negative influences is presented for churn analysis on a macro level but not on an individual level [23]. A churn model is also available to solve unbalanced, scatter and high dimensional problem in telecom datasets [24].…”
Section: Related Workmentioning
confidence: 99%
“…This leads to the importance of managing customer churn. Customer churn prediction has already had fruitful results in the domains of banking, telecoms, insurance, and retail industries (Coussement, Lessmann, & Verstraeten, ; Hung, Yen, & Wang, ; Kumar & Ravi, ; Lee, Kim, & Lee, ; Wei & Chiu, ; Zhang, Liang, Li, Zheng, & Berry, ). For example, Glady, Baesens, and Croux () used customer lifetime value for the modelling and prediction of customer churn.…”
Section: Related Workmentioning
confidence: 99%
“…Data mining and machine learning techniques have been applied in various application domains for knowledge discovery and business intelligence (Gupta, Ahuja, Malhotra, Bala, & Kaur, 2017;Kim et al, 2017;Le, Gabrys, & Nauck, 2017;Lee et al, 2017;Márquez-Vera et al, 2016;Moro, Cortez, & Rita, 2018). Machine learning techniques have also been compared for customer churn prediction (Vafeiadis, Diamantaras, Sarigiannidis, & Chatzisavvas, 2015).…”
Section: Customer Churn Predictionmentioning
confidence: 99%